INOVASI SIB-SAE SEBAGAI STRATEGI MENANGKAL LAJU PERNIKAHAN DINI DI SMAN 1 SUMBER: SMAN 1 SUMBER PROBOLINGGO - DARIS WIBISONO SETIAWAN DAN MUHAMMAD FACHRUR ROZI (Dewan Pendidikan Bondowoso, 2021)
The aims of this study are to (1) describe the innovation governance of the SIB-SAE movement innovation in SMA Negeri 1 Sumber; (2) describe the strategy for implementing the innovation of the SIB-SAE movement at SMA Negeri 1 Sumber. This study uses a qualitative research approach, namely research that requires a depth of appreciation of the interaction between concepts or an in-depth analysis of the relationships of concepts studied empirically. In this study, data collection used several methods such as; (a) observation, (b) documentation, and (c) in-depth interviews. The data analysis technique in this study uses three flow of activities that occur simultaneously, namely; data reduction, data presentation, and conclusion drawing. The results of this study indicate that; (1) The high rate of early marriage has a negative impact on high maternal and infant mortality rates, increased stunting rates, high divorce rates, high potential for student drop out, and low school participation rates. The key to the success of the SIB Movement innovation is the ability of the principal of SMAN 1 Sumber to build the synergy of the three pillars of good governance which is strengthened by the principles of good education governance through the role of the school's organizational structure based on its main functions. (2) The principles of education governance 4K1T (Open, Cooperative, Collaborative, Coordination, and Transparency) strengthen the sustainability of the innovation of the SIB-SAE Movement at SMAN 1 Sumber, (3) The governance strategy for implementing the innovation of the SIB-SAE Movement at SMN 1 Sumber is carried out by strengthening system innovation. Strengthening the system with the principles of good education governance makes all school members move to the success of innovation as an urgent need and will benefit all school members and the wider community. The development of innovation is carried out by implementing activities supporting the innovation program effectively and efficiently without disturbing school finances, both from BOS and BPOPP.